Impact of urine diversion on Biological Nutrients Removal Activated Sludge Wastewater Treatment Plant (BNRAS WWTP) - Mbaya, Andre MK (Department of Civil Engineering, 2014)
This experimental investigation was started to study the impacts urine separated WW [Wastewater] can have on BNRAS WWTPs [Biological Nutrient Removal Activated Sludge Wastewater Treatment Plants] with a UCT and a JHB configuration.